THE USE OF MEDIA FLASHCARDS TO IMPROVE STUDENTS’ VOCABULARY IN SD NEGERI 9 BARRU - Anisa, Beby; Atmowardoyo, Haryanto; Farahdiba, Syarifah (JTechLP: Journal of Technology in Language Pedagogy, 2024)
This study aims to determine whether using flashcard media in primary schools may help kids' vocabulary to grow. The researchers used pre-experimental techniques. Pre- and post-tests were used to collect data. All students at SD Negeri 9 Barru make up the study's population, and 24 grade 4 students were chosen randomly as the study's sample. Following analysis using the significant test formula, the pre-test and post-test results of using flashcard media to increase students' vocabulary revealed that the T-test value was greater, allowing H1 to be accepted. Analysis of the N-gain value also revealed an increase in students' vocabulary. The sample group falls into the average category. The study concludes that using flashcards as a teaching tool increases students' vocabulary, boosts their enthusiasm for learning the language, gives them more confidence to voice their thoughts, and encourages them to be more engaged in learning.